Pengaruh penyuluhan mengenai hipertensi terhadap tingkat pengetahuan masyarakat di Cilolohan, Kota Tasikmalaya - Sukmawan, Yedy Purwandi; Yusuf, Fitra Arif Maulana; Fauziah, Risa Nur; Agustin, Desi; Billah, Tazkia Hasna; Ulfa, Maria; Nurjahan, Nurjahan; Putri, Suci Gandara; Pebrianti, Setiani; Nurjanah, Tamia Febriani; Rojak, Rizki Ahmad; Dianingsih, Meisye Utami; Afifah, Fitri Nur; Anisa, Anis (INDRA: Jurnal Pengabdian kepada Masyarakat, 2025)
Hypertension is a medical condition where blood pressure surpasses the normal range, defined by a systolic pressure of 140 mmHg or higher and a diastolic pressure of 90 mmHg or higher. According to WHO data from 2023, the global prevalence of hypertension was 33%, while in Indonesia, it stood at 34.11%. The high prevalence of hypertension raises concerns about more severe complications, such as stroke, heart disease, and kidney failure. This study aimed to provide health education regarding hypertension and its treatment. The methodology began with a pretest questionnaire, followed by educational sessions using the lecture method and leaflet media, and concluded with a posttest questionnaire. The study results indicated that education on hypertension utilizing the lecture method and leaflet media significantly improved the public's level of knowledge (p < 0.05), with an increase of 18.60%. The health promotion and education about hypertension to the society is effective to increase the knowledge level, and may decrease the cardiovascular events in the future.